A new FGFR inhibitor disrupts the TGF‐β1‐induced fibrotic process - Kim, Mi‐Hyoung (J Cell Mol Med, 2019)
Pulmonary fibrosis (PF) is chronic and irreversible damage to the lung characterized by fibroblast activation and matrix deposition. Although recently approved novel anti‐fibrotic agents can improve the lung function and survival of patients with PF, the overall outcomes remain poor. In this study, a novel imidazopurine compound, 3‐(2‐chloro‐6‐fluorobenzyl)‐1,6,7‐trimethyl‐1H‐imidazo[2,1‐f]purine‐2,4(3H,8H)‐dione (IM‐1918), markedly inhibited transforming growth factor (TGF)‐β‐stimulated reporter activity and reduced the expression of representative fibrotic markers, such as connective tissue growth factor, fibronectin, collagen and α‐smooth muscle actin, on human lung fibroblasts. However, IM‐1918 neither decreased Smad‐2 and Smad‐3 nor affected p38MAPK and JNK. Instead, IM‐1918 reduced Akt and extracellular signal‐regulated kinase 1/2 phosphorylation increased by TGF‐β. Additionally, IM‐1918 inhibited the phosphorylation of fibroblast growth factor receptors 1 and 3. In a bleomycin‐induced murine lung fibrosis model, IM‐1918 profoundly reduced fibrotic areas and decreased collagen and α‐smooth muscle actin accumulation. These results suggest that IM‐1918 can be applied to treat lung fibrosis.